TUMBUH DAN BERKEMBANGNYA SAMPRADAYA DI BALI - I Wayan Sudika (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
Sampradaya in earlier times better known as a sect which is a group of religious beliefs that specializes in worshiping the desired god or god.to get to the path of God. Nowadays the Sampradaya group is often mentioned as a spiritual college and some say it is a flow of belief in God Almighty. The growth and development of Sampradaya based on the theory of relative deprivation, is as a result of a sense of social deprivation in human life. Adaptation theory explains that the choice of community members to join the Sampradaya group, is an appropriate choice, both regarding the objectives to be achieved and the ways in which the pattern of action. Whereas based on the transcendental-praxis reference theory, that sampradaya grows from a transcendental reference that is the transcendence of daily experiences in the natural environment, which can give birth to a knowledge that is spiritual. The principle of sampradaya's teaching is implementing Titi, Tata. Said, Peace purely and consistently. Titi is astiti to Sang Hyang Widhi and parents. Tata is learning to organize, respect for older people, subject to village provisions, or the government. The speech is the words of the priest, leaders and saints or to those who understand better even though they are younger. While Peace is a condition that is based on patience. The practice of teaching is carried out through practice in family life, and practice in life in the communityKeywords: Sampradaya, Bali